Formulation and characterization of thiolated chitosan/polyvinyl acetate based microneedle patch for transdermal delivery of dydrogesterone - Amna Khalid; Hafiz Shoaib Sarwar; Muhammad Sarfraz; Muhammad Farhan Sohail; Aamir Jalil; Yousef A. Bin Jardan; Rabia Arshad; Ifrah Tahir; Zulcaif Ahmad (Elsevier, 2023)
Microneedle patches are promising transdermal drug delivery platforms with minimal invasiveness in a painless manner. Microneedle patch could be a promising alternate route for delivery of drugs having poor solubility and low bioavailability. This research work therefore, aimed to develop and characterize microneedle patch of thiolated chitosan (TCS) and polyvinyl acetate (PVA) for the systemic delivery of dydrogesterone (DYD). TCS-PVA-based microneedle patch was fabricated with 225 needles having a length of 575 µm with the sharp pointed end. Different ratios of TCS-PVA-based patch were employed to investigate the effects of mechanical tensile strength and percentage elongation. The scanning electron microscopy (SEM) revealed intact sharp-pointed needles. In vitro dissolution studies of microneedle patch (MN-P) were carried out by modified Franz-diffusion cell revealing the sustained release of DYD 81.45 ± 2.768 % at 48 hrs as compared to pure drug that showed 96.7 ± 1.75 % at 12 hrs. The transport of DYD (81%) across skin reaching the systemic circulation was evaluated through ex vivo permeation studies of MN-P. The skin penetration study through the parafilm M method showed good penetration with no deformation and breakage of needles along with no visible signs of skin irritation. Histological study of mice skins clearly showed the deeper penetration of needles into the skin. In summary, as-prepared MN-P show potential in developing an effective transdermal delivery system for DYD.